2018
DOI: 10.3892/mmr.2018.9355
|View full text |Cite
|
Sign up to set email alerts
|

In�vitro and in�vivo study of the expression of the Syk/Ras/c‑Fos pathway in chronic glomerulonephritis

Abstract: Chronic glomerulonephritis (CGN) is the most common form of glomerular disease; however, its associated molecular mechanisms remain unclear. Spleen tyrosine kinase (Syk) is a key mediator of B-receptor signaling on the surface of inflammatory cells. The primary target for R406 is Syk. The aim of the present study was to investigate the molecular mechanisms involved in a rat model of CGN induced by adriamycin (ADR) and in the rat glomerular mesangial cell line, HBZY-1, stimulated by lipopolysaccharide (LPS). CG… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 26 publications
0
6
0
Order By: Relevance
“…Caspase-3 is involved in the pathogenesis of doxorubicin-induced cardiomyopathy [ 59 , 60 ] and nephropathy [ 61 ]. As a more proximal step in the cell response to doxorubicin toxicity, p53 overexpression plays a major role in developing dilatative cardiomyopathy and chronic kidney disease [ 11 ] mainly through its’ genomic integrity monitoring activity [ 62 ].…”
Section: Discussionmentioning
confidence: 99%
“…Caspase-3 is involved in the pathogenesis of doxorubicin-induced cardiomyopathy [ 59 , 60 ] and nephropathy [ 61 ]. As a more proximal step in the cell response to doxorubicin toxicity, p53 overexpression plays a major role in developing dilatative cardiomyopathy and chronic kidney disease [ 11 ] mainly through its’ genomic integrity monitoring activity [ 62 ].…”
Section: Discussionmentioning
confidence: 99%
“…In order to clarify the relationship between miR-339-5p and CGN, HBZY-1 cells induced by LPS were used as CGN experimental model in this study [20]. qRT-PCR was used to detect the expression levels of miR339-5p in the Control group and the Model group.…”
Section: Mir-339-5p Was Signi Cantly Downregulated In Hbzy-1 Cellsmentioning
confidence: 99%
“…In addition, Syk is an important part of the middle Syk/Ras/c-Fos signal pathway. Through bioinformatics prediction and analysis in the early stage, our research group found that miR-339 had the highest binding degree with Syk, and studied the in uence of Syk/Ras/c-Fos signaling pathway on HBZY-1 cells [20], but did not discuss the pathogenesis of CGN from the genetic level. Therefore, through the establishment of LPS-induced HBZY-1 cell model, this paper expounds the pathogenesis of CGN from the point of view of miR-339-5p and Syk/Ras/c-Fos signal pathway.…”
Section: Syk Downregulation Reversed the Effects Of Mir-339-5p On Hbzy-1 Cellsmentioning
confidence: 99%
“…The rat glomerular mesangial cells line (HBZY-1) was obtained from the Cell Bank of FuHeng Biology (Shanghai, China) and incubated with Dulbecco's modified Eagle's/F-12 medium [10% (v/v) fetal calf serum and 1% (v/v) antibiotics mixture] in 95% air and 5% CO2 at 37 °C. The lipopolysaccharide (LPS)-stimulated HBZY-1 cell model, which is often used for in vitro study of chronic glomerulonephritis, has been mentioned in our previous study (Gao et al 2018). Our experiment was separated into three groups: the control group (HBZY-1 cells were treated with normal rat serum for 24 h), the model group (HBZY-1 cells were treated with 0.5 μg/mL LPS for 48 h and then added to normal rat serum for 24 h), and the JQHF treatment group (HBZY-1 cells were treated with 0.5 μg/mL LPS for 48 h and then added to JQHF-medicated serum for 24 h).…”
Section: Cell Culture and Treatmentmentioning
confidence: 99%